Spray-grown highly oriented antimony-doped tin dioxide transparent conducting films - Parra, Rodrigo; Leinen, Dietmar; Ramos-Barrado, José Ramón; Martín-Jiménez, Francisco de Paula (Elselvier, 2020)
Undoped and Sb-doped tin dioxide films of varying thickness with a remarkable crystallographic orientation in the [200] direction were grown by spray-pyrolysis from tin(II) chloride solutions. Films grown on silica-coated glass substrates were completely crystalline and showed a higher degree of orientation with respect to films that were grown on uncoated glass. The presence of the silica barrier was seen to have increased the degree of orientation and to have enhanced the resulting electrical properties. Transmission electron microscopy revealed that the silica layer may have played the crucial role of a nucleation layer. Moreover, the developed micro structures were correlated with the optical and electrical behaviour of the films. Dense conducting films with thicknesses between 280–450 nm and visible transmittances of 80-70 % showed resistivities of about 10−3 Ωcm
Keywords: Películas delgadas; Transparent conducting oxides; Tin oxide; Spray-pyrolysis; Thin films